HUBUNGAN BEBAN KERJA, STRESS KERJA DAN WORK LIFE TERHADAP KINERJA GEN Z (STUDI KASUS DI KOTA BANJARMASIN) - Rosalina, Eyen; Anggraeni, Julia (POLITEKNIK LP3I JAKARTA, 2026)
The global labor market dynamics in 2026 face significant challenges regarding the high rate of turnover intention among Generation Z. This study aims to analyze the relationship between workload, meaningful work, and job stress on turnover intention, with job satisfaction as a mediating variable among Generation Z employees in Banjarmasin. Using an explanatory quantitative approach with the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method, data were collected from 160 respondents through purposive sampling in February 2026. The results indicate that workload and job stress have a significant positive effect on turnover intention, while meaningful work has a significant negative effect as the strongest stay factor. Job satisfaction is proven to function as a crucial partial mediator in bridging the influence of these three variables on turnover intention. These findings emphasize that for Gen Z, mental health and role significance are prioritized over physical workload over. Management is advised to prioritize psychological support and job enrichment to retain young talent